Achieving our country : leftist thought in twentieth century America - Rorty, Richard (Harvard University Press, 1998)
Must the sins of America's past poison its hope for the future? Lately the American Left, withdrawing into the ivied halls of academe to rue the nation's shame, has answered yes in both word and deed. In Achieving Our Country, one of America's foremost philosophers challenges this lost generation of the Left to understand the role it might play in the great tradition of democratic intellectual labor that started with writers like Walt Whitman and John Dewey.